2011
DOI: 10.1038/cr.2011.125
|View full text |Cite
|
Sign up to set email alerts
|

Generation of induced pluripotent stem cells from bovine embryonic fibroblast cells

Abstract: Embryonic stem cell (ES cell) lines were first generated by culturing mouse inner cell mass (ICM) on feeder layers in 1981 [1]. However, in large domestic animals, attempts to establish ES cell lines from ICM of blastocysts or the later epiblast have not been successful. This has hindered the efficient production of genetically modified livestocks by using ES-based approaches. Recently, it was found that ectopic expression of various combinations of transcription factors is able to reprogram somatic cells to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
113
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 12 publications
6
113
0
1
Order By: Relevance
“…The biPS-1 cell line was established in medium supplemented with bFGF (8 ng/mL) and hLIF (1000 U/mL), suggesting that the bovine iPSCs use different pluripotency signaling pathways and require different culture conditions than human or murine iPSCs. Speculatively, bovine iPSCs may need NANOG on top of OSKM, and FGF and knockout serum to maintain the pluripotency status (Han et al, 2011). The exogenous genes used for reprogramming in the current study were not silenced as reported in previous studies in which viral vectors had been used for reprogramming (Cao et al, 2012;Han et al, 2011;Sumer et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The biPS-1 cell line was established in medium supplemented with bFGF (8 ng/mL) and hLIF (1000 U/mL), suggesting that the bovine iPSCs use different pluripotency signaling pathways and require different culture conditions than human or murine iPSCs. Speculatively, bovine iPSCs may need NANOG on top of OSKM, and FGF and knockout serum to maintain the pluripotency status (Han et al, 2011). The exogenous genes used for reprogramming in the current study were not silenced as reported in previous studies in which viral vectors had been used for reprogramming (Cao et al, 2012;Han et al, 2011;Sumer et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
“…Previously, bovine iPSCs have been derived from bovine fetal and adult fibroblasts by retroviral or lentiviral transduction (Cao et al, 2012;Han et al, 2011;Sumer et al, 2011) or nonintegrating plasmids (Huang et al, 2011;Wang et al, 2013). Retroviral and lentiviral vectors are the most commonly used gene delivery systems because they have high transduction rates; lentiviral vectors even allow transduction of nonproliferating cells (Coroadinha et al, 2010;Segura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to highlight these stem cell papers in this special issue as stem cell research is intrinsically connected to the study of cell signaling and disease. The collection of a large number of stem cell papers also reflects the fact that stem cell research has become an important part of the growing content of Cell Research, as highlighted by a large number of important discoveries published in the journal in the past year alone, such as the successful generation of iPS cells with a single factor Oct4 [3,4], efficient generation of human iPS cells from blood cells via a non-integrating method [5], generation of functional platelets from hESCs [6], directed differentiation of atrial and ventricular myocytes from hESCs [7], the successful generation of ovine, hircine and bovine iPS cells [8][9][10], somatic cell reprogramming using electrofused blastomeres [11], improved methods for iPS cell generation [12,13], gener-ating iPS cells using Bmi1 [14], comprehensive analyses of chromatin state dynamics in hESC differentiation [15], characterization of neuroblasts in the adult human brain [16], identification of lectin biomarkers for human pluripotent stem cell isolation [17], and efficient correction of disease-causing genetic mutations in patient iPS cells [18].…”
mentioning
confidence: 99%